2017
DOI: 10.1167/iovs.16-21255
|View full text |Cite
|
Sign up to set email alerts
|

Course of Sodium Iodate–Induced Retinal Degeneration in Albino and Pigmented Mice

Abstract: PURPOSE. To characterize the course of sodium iodate (SI)-induced retinal degeneration in young adult albino and pigmented mice. (25, 50, and 100 mg/kg) were performed in 7-to 8-week-old BALB/c and C57Bl/6J mice. Retinal function and structure was assessed at baseline, 24 hours, 3 days, 1, 2, 3, and 4 weeks postinjection by optokinetic tracking response, ERG, optical coherence tomography (OCT), and histologic and immunohistochemical techniques. METHODS. Single intraperitoneal (IP) injections of SI RESULTS.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 47 publications
(51 reference statements)
6
91
0
Order By: Relevance
“…The intravenous injection of NaIO 3 creates widespread RPE, photoreceptor, and CC atrophy. 2 5 , 17 , 18 This is in sharp contrast to the focal, succinct atrophic areas surrounded by intact, healthy RPE and CC seen in GA. The border region between atrophic and normal tissue is most interesting for studying disease progression of GA, as this is where degeneration is actively occurring.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The intravenous injection of NaIO 3 creates widespread RPE, photoreceptor, and CC atrophy. 2 5 , 17 , 18 This is in sharp contrast to the focal, succinct atrophic areas surrounded by intact, healthy RPE and CC seen in GA. The border region between atrophic and normal tissue is most interesting for studying disease progression of GA, as this is where degeneration is actively occurring.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, a well-characterized, cost-effective, and rapid degeneration animal model of GA would be very useful. Sodium iodate (NaIO 3 ) injection has been extensively used as a preclinical model of RPE degeneration and GA. 2 5 Different delivery routes and various doses of NaIO 3 have been reported to induce RPE changes in a variety of mammalian species. 2 7 NaIO 3 is thought to directly affect the RPE cells with secondary effects on photoreceptors and the CC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported on the time-and dosedependent changes in the NaIO 3 -induced retinal degeneration. 13,19,20 The RPE degeneration induced by NaIO 3 leads to the production of pigment-rich substances, 13,21,22 and both the thickness of the photoreceptor outer and inner segments and the outer nuclear layer are reduced. 13,22 In addition, exposure of the RPE cells to NaIO 3 induces a loss of the integrity of the RPE cells and an enlargement of RPE cells.…”
mentioning
confidence: 99%
“…(2020) 10:3588 | https://doi.org/10.1038/s41598-020-60579-1 www.nature.com/scientificreports www.nature.com/scientificreports/ photoreceptors, SI also provokes choriocapillaris atrophy 27,28 , necrosis of the inner retina 24,29 , and panretinal degeneration 24,30 . It has been reported that various doses and routes of administration of SI cause retinal toxicity in many different experimental animals (e.g., sheep 25 , rabbits 25,31 , rats 30,32 , and mice 23,29,33 ). Most studies have employed relatively high doses of SI (50-100 mg/kg) and have reported rapid RPE damage characterized by the defragmentation and loss of RPE cell nuclei.…”
Section: Discussionmentioning
confidence: 99%